Study on structure defect in commercial building in Malaysia - Che Nurwani, Che Soh (2018)
Malaysia is among one of the development countries that growing advanced in all sectors especially in construction industry. Structure defect is one of the issues that relate to commercial building and significantly needed attention. Structure defect can occur because of the design error, defective materials, improper use or installation of materials, lack of adherence design from the contractor or any combination of these cause. Next, issues about poor workmanship always associated with small contractor as they not well trained to be in construction industries. In addition, improper building design also contribute to the structure defect of a building. The objective is to identify type of structure defect in commercial building, identify factor affecting structure defect and to analyse the structure defect that always happen in commercial building. A quantative research was conduct by sending 50 sets of questionnaire to the respondents. The result form 50 set of completed questionnaire were used for the qualitative analysis.In this research shown that the highest ranked for the common type of structure defect in commercial building is cracking of beam. Follow by, cracking of column, honeycomb in concrete and racking of wall. The most significant factor affecting the structure defect in commercial building is weather and environment condition. In conclusion, this structure defect problem would be an important thing and should minimize the structure defect by knowing the ways to overcome when structure defect occur immediately.